Contribution analysis of the long-term changes in seasonal runoff on the Loess Plateau, China, using eight Budyko-based methods - Wu, Jingwen; Miao, Chiyuan; Wang, Yamei; Duan, Qingyun; Zhang, Xiaoming (Journal of hydrology (Amsterdam), 2017)
•Eight commonly used Budyko-based methods were reviewed and summarized.•Eight methods were applied to evaluate streamflow variations on the Loess Plateau.•Quantitative contributions were similar across methods during the high-flow season.•Human activity contributed on average 73% of the decrease in the high-flow season.•Changes in runoff were more sensitive to precipitation than to PET. Over the last five decades, runoff from the Loess Plateau has greatly decreased because of changes in the climate and intensive human activities. Comprehending and distinguishing the relative impacts of climate change and human activities on runoff is essential to adapt water-resource management and soil-and-water conservation projects to climate change. In this study, we used a technique involving integrated climate elasticity and eight Budyko-based methods to assess the relative impacts of climate change and human activities on runoff changes during high-flow and low-flow seasons in 17 catchments across the Loess Plateau during the period of 1961–2013. The results showed that, on average, runoff in the high-flow season exhibited a significant downward trend in 15/17 catchments, with an average decrease of 0.63mm/yr. In contrast, the decrease was 0.29mm/yr for the low-flow season. We also found that changes in runoff were more sensitive to variations in precipitation than variations in potential evapotranspiration, in both high-flow and low-flow seasons. The quantitative contributions from climate change and human activities as calculated by the eight Budyko-based methods were relatively similar during the high-flow season, but varied across catchments in the low-flow season. The results showed that, during the high-flow season, human activities had a greater impact on runoff changes than climate change, accounting for about 73% of the total decrease. However, in the low-flow season, which exhibits significantly increased potential evapotranspiration (p<0.01) and decreased precipitation, the influence of climate change on runoff changes was greater than the influence of human activities. The discrepancies between the results obtained via eight Budyko-based methods and the resulting uncertainties in the quantitative attributions are also discussed.